Aerosol particles observed onboard the research vessel Mirai over the Southern Ocean in the austral summer of 2017 ... - Miyakawa, Takuma; Taketani, Fumikazu; Tobo, Yutaka; Matsumoto, Kazuhiko; Yoshizue, Momoka; Takigawa, Masayuki; Kanaya, Yugo (Zenodo, 2023)
We have compiled a dataset of field observations to measure aerosol particle size distributions and to collect the aerosols for the following laboratory analyses to quantify the chemical composition and ice nucleating properties of aerosols over the Southern Ocean in the austral summer of 2017 as a part of the research cruise of Japanese research vessel (R/V) Mirai (Cruise number of MR16-09 leg3). The particle size distributions (PSDs) of the submicron aerosols (14–737 nm in the electrical mobility diameter) were measured using a scanning mobility particle sizer, SMPS, which is composed of a differential mobility analyzer, DMA (model 3081, TSI Inc., Minnesota, USA) and a condensation particle counter, CPC (model 3010, TSI Inc.). Since a custom-made inlet system was installed in front of the SMPS, the PSDs of total and non-volatile aerosols upon heating at the 300°C were alternatively measured every 5 min. The PSDs of the coarse fluorescent and non-fluorescent particles (700–3000 nm in the optical diameter) ... : The data set is used in Miyakawa et al. (2023). Measurements of Aerosol Particle Size Distributions and INPs Over the Southern Ocean in the Late Austral Summer of 2017 on board the R/V Mirai: Importance of the marine boundary layer structure. Earth and Space Science, in review. This study was supported by the JSPS KAKENHI grant numbers JP26281018, JP18H04143, and JP19H05699, and carried out as a part of the Arctic Challenge for Sustainability (ArCS) Project (JPMXD1300000000). ...